The Resilience of Democratic Values Under Difficult Conditions. The Case of Guatemala 2012-2021 - Meléndez, Carlos (Revista Latinoamericana de Opinión Pública, 2023)
This article describes the evolution of democratic attitudes in Guatemala between 2012 and 2021 and identifies, at the political system level, the contextual factors that have contributed to changes in attitudes over time. For this purpose, we trace the linkages between recent political, economic, and social development indicators/trends and public opinion data. Based on cluster analysis of nationally representative survey data, we group of citizens with distinct patterns of democratic attitudes. Those “institutionalists”, who express consistent support for democratic institutions, comprise the largest share of respondents in all the examined years, although that share decreases in the more recent surveys. The research sustains that democratic values among Guatemalans are resistant despite the establishment’s attempts to hinder anti-corruption processes. Civic mobilization demanding accountability, justice, and respect of electoral results confirm this democratic resilience, despite the institutional setbacks.